An Empirical Investigation of Mispricing in Stock Futures at the National Stock Exchange - Nandan, Tanuj; Agrawal, Puja; Jindal, Shakshi (Indian Journal of Finance, 2015)
This paper is an attempt to study the mispricing in stock futures of India. The cost of carry model was operationalized in the present study. Any deviation from the theoretical price so arrived at connotes mispricing. In-depth analysis was conducted with respect to the frequency and magnitude of mispricing. Furthermore, the results were charted across variables like maturity and with respect to basis. Non parametric tests were applied to establish statistical significance of the findings. The findings indicate that there existed significant mispricing in the stock futures studied. Most of the stock futures contracts were underpriced. These mispricing signals seemed to be largely unutilized by the arbitrageurs due to short selling restrictions at Indian bourses. A clear relationship was observed between basis and mispricing as well as maturity and mispricing. The implications of the findings can be manifold for all the participants in the derivatives market. The paper concluded with limitations of the study and directions for future research.